Refleksitas Iman dan Ilmu Serta Apresiasinya Berdasarkan Studi Al-Qur’an dan Al-Hadits - Hanafi Hanafi; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research investigates the connection between faith and knowledge as outlined in Surah Al-Mujadalah, particularly focusing on the two key conditions for attaining higher ranks in the sight of Allah SWT: tafassuh fil majlis (creating space in gatherings) and bersegera dalam melakukan kebaikan (rushing to do good deeds). These principles emphasize that faith and knowledge should not be mere theoretical concepts but must be reflected in practical actions that benefit society and align with Islamic values. The analysis uses a tafsir approach and social context to elucidate how these conditions serve as indicators of true faith and knowledge. By examining relevant scholarly opinions and historical contexts, this paper explains the significance of these conditions in fostering social harmony and personal development, ultimately leading to spiritual elevation. The application of these principles in daily life results in a positive societal impact and the elevation of one's status in the eyes of Allah SWT. Thus, the study reinforces that faith and knowledge, when paired with humble